Application of FOCUS-PDCA program to reduce the incidence of ventilator-associated pneumonia in ICU patients (运用Focus-PDCA降低重症监护室患者呼吸机相关性肺炎发生率) - WANG Jing (王静); CAO Zhuan (曹转); YAN Ailing (闫爱玲); FAN Xiaoyan (范小燕); XU Yuanle (许远乐) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of FOCUS-PDCA program to reduce the incidence of ventilator-associated pneumonia in ICU patients. Methods The incidence of ventilator-associated pneumonia in ICU patients during 2016 and 2018 were retrospectively analyzed. A FOCUS-PDCA project management team was established to improve the airway management of ICU patients with ventilation. Results A bundle of prevention measures and regulations had been established. The incidence of VAP in ICU patients was decreased form 4. 68‰ to 2. 28‰. Conclusion The Focus-PDCA program is effective to reduce the incidence of ventilator-associated pneumonia in ICU patients (目的 探讨Focus-PDCA管理程序降低重症监护室患者呼吸机相关肺炎的发生率的效果。方法 通过发现重症监护室2016年-2018年呼吸机相关肺炎的发生率逐年递增问题, 2019年及时组建专项管理小组, 利用Focus-PDCA管理工具进行改进。结果 规范重症监护室呼吸机相关性肺炎的预防措施, 呼吸机相关肺炎发生率从4. 68‰下降至2. 28‰。结论 重症医学科实施Focus-PDCA管理能有效降低患者呼吸机相关性肺炎的发生率。)